Managing products return: an examination of the practices of online retailers - Mursalin, Md. Jabir Al (Journal of System and Management Sciences, 2016)
This article was published in Journal of System and Management Sciences [© 2014 Journal of System and Management Sciences] and the definite version is available at : http://www.aasmr.org/jsms/Vol4/No.2/JSMS_VOL4_NO2_005.pdf The article website is at: http://www.aasmr.org/jsms/